Epidemiology, economic losses due to Haemorrhagic Septicemia and cost-benefit analysis of interventions in dairy animals of Punjab - MALIK, M H; JAN, M H; VERMA, H K; SHARMA, R K (The Indian Journal of Animal Sciences, 2021)
The epidemiological features and financial losses due to Haemorrhagic Septicemia (HS) in dairy animals of Punjab were studied using the primary data collected from 720 livestock owners/ dairy farms. The overall incidence and case fatality rate (CFR) risk of HS among dairy animals was 5.45 and 45.15%, respectively. Incidence risk of HS on the species basis varied significantly and was observed highest in buffaloes (6.27%), followed by cross bred (4.67%) and indigenous cattle (3.91%). The overall financial loss due to HS per affected animal per year was ` ₹ 5111.64±482.32. However, the mean economic losses per animal per year affected varied significantly among different categories of animals, and was highest in buffalo (`₹ 7265.08±735.27), followed by cross bred (` 5799.55±447.48) and lowest in indigenous cattle (`₹ 2270.30±405.22). At species level, the largest component of the economic losses were due to mortality loss of animals (69.42% in cross bred, 63.15% in indigenous cattle and 70.40% in buffaloes), followed by treatment cost and reduction of milk yield. On benefit cost analysis of control measures, higher BCA ratio was observed in buffalo, followed by crossbred and indigenous cattle. It may be concluded that poor understanding of the disease and lack of effective control measures such as timing and potency of vaccination are some of the factors impacting upon the economics of dairy farming in Punjab state. Training and extension activities should backup the efforts to control this dreadful disease.